(untitled) (Journal of Oriental Studies, 2018)
Changes in the world arena in the late 20th century led to a change in the theory of international relations. In this article, the authors touched on one of the new theories, as the concept of “soft power”. The authors tried to reveal the gist of this concept, which in their opinion consists of excluding the “hard power” of countries towards to other countries, also in using the specialties of the culture of their people and to show its attractiveness on the world stage. The authors show the strategy of “soft power” in the example of South Korea, which with the help of its instruments achieved significant achievements in world politics. Also in this article, reviewed the theoretical foundations of the South Korean strategy “soft power” and its role in forming the positive image of the country at the international level.